Emotional contagion model for group evacuation simulation (Informatica, 2017)
The key role of emotions in decision-making process of human beings has been highlighted recently. Our research focuses on fear-related emotions and their positive impact on the survival capabilities of human beings in case of crisis situations. In this paper, we proposed a new model of emotional contagion based on some main findings in social psychology. This model was formalized mathematically, implemented and tested in the GAMA agent-based simulation platform in the context of evacuation simulation. We assessed experimentally the impact of three factors (emotion decay, environment, neighbors' emotional contagion) on emotion dynamics at individual and group levels. The experimental results allow us to understand the emotional contagion of agent group in several scenarios. The proposed model will help us to better study the impact of emotional contagion on evacuation safety in evacuation simulation.The entire theoretical model has been implemented in the simulation platform GAMA.